LISA improves statistical analysis for fMRI - Gabriele Lohmann (Nature Portfolio, 2018)
Functional magnetic resonance imaging (fMRI) is a powerful technique for measuring human brain activity, but the statistical analysis of fMRI data can be difficult. Here, the authors introduce a new fMRI analysis tool, LISA, which provides increased statistical power compared to existing techniques.